Tinjauan perubahan cara bercocok tanam pada lanskap agrikultur di desa enclave Taman Nasional Bromo Tengger Semeru, Ngadas, Kabupaten Malang - Santoso, Dian Kartika; Antariksa, Antariksa; Utami, Sri (Jurnal Arsitektur Lansekap; Vol.5, No.2, Oktober 2019DO - 10.24843/JAL.2019.v05.i02.p11, 2019)
A review of cultivation changes in agricultural landscapes in the enclave village of Bromo Tengger Semeru National Park, Ngadas, Malang Regency Ngadas village is one example of an agricultural village located in the mountains. Ngadas village is located in the enclave of Bromo Tengger Semeru National Park (TNBTS) in the Malang Regency, East Java. The dependence of the community on agricultural land makes Ngadas have a strong agrarian image. Ngadas people do more activities in the fields than in the house. As basic landscape units in the form of mountains, they have a vulnerability if not used wisely. The problem of vulnerability to erosion in the agricultural landscape, makes Ngadas Village interesting to study. Primarily, regarding the relationship of landscapes and land conservation efforts that must be made to a complex agricultural landscape. Therefore, there is a need for research that focuses on efforts to conserve land, especially in an agricultural landscape. Research is conducted through qualitative methods with spatial and qualitative descriptive comparative analysis. The results of the study show that changes in farming methods have several disadvantages that can cause land degradation and reduced productivity in each period, including the shifting cultivation system to reduce nutrients, upper slopes planted with tubers and monoculture agriculture. Therefore, it is necessary to have the right recommendations, namely planting upper slopes with hard wood plants, planting with polyculture systems, and agroforestry systems applied on the upper slopes.